2023
DOI: 10.1021/acs.jpcc.3c05222
|View full text |Cite
|
Sign up to set email alerts
|

Steric and Electronic Effect in Unsymmetrical Squaraine Dyes for Dye-Sensitized Solar Cells

Indrajeet S. Nawghare,
Ambarish Kumar Singh,
Ashakiran Maibam
et al.

Abstract: Functionalizing the light harvesting sensitizers with additional electron-donating or -withdrawing groups is a potential approach to modulate the photophysical and electrochemical properties which in-turn optimizes the driving force associated with the charge injection and dye-regeneration processes at the dye-TiO 2 / electrolyte interface and the photovoltaic device performance in dyesensitized solar cells (DSSCs). Furthermore, modulated electronic levels of the dyes provide an opportunity to reduce the overp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Thus, we propose to these molecules as promise natural dye and thus a computational study about photoexcitation and electron injection will be fundamental to understand the role of carotenoids as sensitizing on TiO 2 . [42,43]…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we propose to these molecules as promise natural dye and thus a computational study about photoexcitation and electron injection will be fundamental to understand the role of carotenoids as sensitizing on TiO 2 . [42,43]…”
Section: Introductionmentioning
confidence: 99%
“…However, to control the aggregation of dyes by anchoring group engineering, a set of selenorhodamine dyes have been developed, and they showed that the H-aggregated dyes can participate in photocurrent generation . Furthermore, including alkyl groups and electron-donating groups in squaraine dye structures helps minimize the aggregation of sensitizers on TiO 2 and modulates the electronic properties of the dyes for enhanced device performance. , We designed and synthesized two novel pyridine-based dyes SD1 and SD2 and a carboxylic acid-based visible-light-active dye SD3 , in which pyridine binds mostly to the Lewis acid sites of TiO 2 while the carboxylic acid binds to the Brønsted acid sites of TiO 2 . SD1 and SD2 dyes having pyridyl anchoring groups were used to study their cosensitization using a blue dye, that is SD4 , having a carboxylic acid anchoring group (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Dyes SD1 or SD2 were cosensitized with SD4 as the absorption spectra complemented each other ( SD1 and SD2 absorb in the visible region, whereas SD4 absorbs in the far-red region) (Figure ). The dye SD4 possesses indoline donor groups with long alkyl chains, which have been proven to be useful in iodine-based electrolyte systems, particularly in reducing the charge recombination process in a DSSC device …”
Section: Introductionmentioning
confidence: 99%